What predicts the clinical benefits of PARP inhibitors in platinum-sensitive recurrent ovarian cancer: A real-world single-center retrospective cohort study from China - Zhang, Depu; Li, Shuo; Zhang, Xinxin; Peng, Jingwei; Zhang, Shiqian (Frontiers in Oncology, 2022)
Objective: This study assessed the real-world application, effectiveness, and safety of olaparib and niraparib as maintenance therapy in patients with platinum-sensitive recurrent ovarian cancer (PSROC) in China and investigated clinical factors associated with prolonged benefits of poly ADP-ribose Polymerase (PARP) inhibitors to help guide clinician treatment-decision making in daily practice. Methods: This real-world single-center retrospective cohort study was conducted at Shandong Cancer Hospital and Institute. Archival data of consecutive patients diagnosed with PSROC who achieved a complete response (CR) or partial response (PR) after the last platinum-based chemotherapy and treated with olaparib or niraparib as maintenance therapy from August 2018 to September 2021 were collected. Results: Overall, 106 women were included in the cohort, 72 (68%) patients were treated with olaparib, while 34 (32%) received niraparib; 99.1% of the patients were diagnosed with high-grade serous carcinoma, and 73.6% had FIGO stages III-IV. Approximately 71.7% of the patients had received PARP inhibitors after the second platinum-based line and 44.3% of the patients achieved a CR in their last platinum-based therapy. The median platinum-free interval (PFI) after the penultimate platinum-based therapy was 10 (95% CI: 10-13.6) months. Median PFS was 21 (95% CI: 13-24.5) months and median CFI was 22 (95% CI: 16-26.5) months. Consistent with the univariate analysis, the multivariate analysis identified three independent factors associated with prolonged progression-free survival (PFS) and chemotherapy-free interval (CFI): breast cancer susceptibility gene (BRCA) mutant type (p=0.005 and p=0.003), PFI≥12 months (p=0.01 and p=0.006) and CR to last platinum-based therapy (p=0.016 and p=0.019). There was no appreciable difference in any grade 3-4 hematological AE between patients who received olaparib and niraparib. Conclusions: Maintenance treatment with olaparib and niraparib is effective and well tolerated for PSROC patients in real-world clinical practice. Three clinical factors were identified that predicted prolonged survival under maintenance therapy with PARP inhibitors: BRCA mutant type, PFI≥12 months and CR to last platinum-based therapy. These findings should be further confirmed with an appropriately powered analysis in studies with larger sample sizes.